PROBLEMATIK DESENTRALISASI PENGELOLAAN SUMBERDAYA HUTAN DI PAPUA - Sudiyono, Sudiyono (P2KK LIPI, 2007)
The decentralization of forestry sector in Papua Province has been executed by the Community Forestry Programme. To support this programme, the Indonesian government issued a series of regulations; Government Regulation (PP No: 6/1999) on the Small Scale Logging Consession Permit, the Ministry of Forestry Decision Letter No: 677/Kpts – II/1998 on Community Forestry Programme, and Forest Reform Act No: 41/1999. However, the implementation of these policies had caused many problems, among athers: (1) inconsistency of government policies, which had caused authority conflict between local governments and central government in managing the forest resource; (2) policies that caused illegal logging activities; (3) an increase of policy manipulation practice. In the end, this policy have failed to create both quality improvement of the local people social economic life as well as a sustainable forest development. This article is focused to discuss questions on how the local government implement these policies, and what are the problems faced by the settlers in and around of the forest. Keywords: decentralization, forestry, Papua, Community Forestry